İNTRALOBER PULMONER SEKESTRASYON VAKASI VE LİTERATÜRLERİN GÖZDEN GEÇİRİLMESİ - SİPAHİ DEMİRKÖK, Sevtap and GÜRSU, Rıza and KÖKSAL, Cengiz and GÜREL SAYIN, Ayla and KARAYEL, Tuncer (Cerrahpaşa Medical Journal, 2014)
Background.- Pulmonary sequestrations are congenital lesions comprised of nonfunctional lung tissue that does not communicate with the normal tracheobronchial tree and has a systemic arterial blood supply. Intralobar sequestration is the most seen type of pulmonary sequestrations. Surgical resection is the only choice of management. An abnormal systemic artery supplies the blood for the sequestrated lung tissue. This artery is usually come from the thoracic aorta. Observation.- In this paper a 37 year old female patient whom was diagnosed as an intralobar pulmonary sequestration and whose abnormal artery is from was presented, and the literature was reviewed.